2016
DOI: 10.1128/mcb.00589-15
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuronal Cell Cycle and Apoptosis by MicroRNA 34a

Abstract: The cell cycle of neurons remains suppressed to maintain the state of differentiation and aberrant cell cycle reentry results in loss of neurons, which is a feature in neurodegenerative disorders like Alzheimer's disease (AD). Present studies revealed that the expression of microRNA 34a (miR-34a) needs to be optimal in neurons, as an aberrant increase or decrease in its expression causes apoptosis. miR-34a keeps the neuronal cell cycle under check by preventing the expression of cyclin D1 and promotes cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…The neurons from Tg AD exhibited elevated expression of cleaved caspase 3 as reported previously (Modi et al . ), which was significantly prevented by p27 depletion (Fig. a, panel d, lane 3 vs. lane 2).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The neurons from Tg AD exhibited elevated expression of cleaved caspase 3 as reported previously (Modi et al . ), which was significantly prevented by p27 depletion (Fig. a, panel d, lane 3 vs. lane 2).…”
Section: Resultsmentioning
confidence: 86%
“…; Modi et al . ). The neurons from Tg AD exhibited elevated expression of cleaved caspase 3 as reported previously (Modi et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Modi et al. reported that miR‐34a targeted cyclin D1 and promoted neuronal differentiation by inhibiting cell cycle reentry, while downregulation of miR‐34a caused cell cycle‐related neuronal apoptosis 46. Fear memory consolidation was also mediated by miR‐34, which inhibits the Notch signaling pathway in the amygdala 47.…”
Section: Discussionmentioning
confidence: 99%